EFEKTIVITAS KOMPOSTER TAKAKURA DAN KOMPOSTER SEDERHANA DALAM PEMBUATAN KOMPOS SAMPAH ORGANIK - islam, fahrul; Nurita; Akbar, Fajar; Mubarak, Faisal (Poltekkes Kemenkes Bengkulu, 2023)
Garbage is an inseparable part of people's lives, especially in urban areas. If waste is not handled properly and correctly from the source of waste, it will cause problems to health, social, economic and beauty. The purpose of this study was to determine the effectiveness of takakura composters and simple composters in making compost from organic samapah. This research was conducted at the Workshop of the Department of Environmental Health, Poltekkes, Ministry of Health, Mamuju. Type of research: experimental research to assess the effectiveness of takakura composters and simple composters in composting organic waste. Method: The subjects of this study are takakura composters and simple composters in making organic waste compost. Data obtained from the results of field analysis are processed and presented in the form of tables, to be further processed descriptively so that conclusions and suggestions can be drawn. Result: takakura composter has a composting time of 22 days, with a blackish-brown color, earthy smell, pH 7.5, temperature of 29o C and moisture content of 49.3% and 34%. As for the simple composter, it has a composting time of 28 days, with a blackish-brown color, earthy smell, pH 7, temperature of 28o C, and moisture content of 44% and 37%. Conclusion: takukara composters are better at composting compared to simple composters in terms of composting time. It is recommended for future research to conduct compost-related research by comparing the treatment of variations in the use of E-M4 activator in each compost.